(untitled) (Euro-Latin American Journal of Administrative Law, 2022)
Today, sustainable development is a guiding idea that affects Law, especially Public-Administrative Law, projecting itself to all state activity. The conceptual delimitation, its meaning, its legal nature, its purpose, and foundation is essential for the analysis of the scope of the obligations assumed by the Argentine State in international treaties and its responsibility. In this article we address all these aspects of the notion of sustainable development and its reception in the Argentine legal system, and its impact on state activity.